Особливості будови кореневих систем у вегетативно розмножених культиварів роду Juniperus L. - Ponomarenko, V.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Results of the comparative morphological analysis of root systems of vegetatively reproduced junipers of different habitual shapes are given in the article. Five types of root systems are described in accordance with root distribution along the radius and the layers of soil.